PHILOSOPHICAL ANALYSIS OF THE IDEOLOGIES OF "PAN-ISLAMISM" AND "PAN-TURKISM" (TAMADDUN NURI JURNALI, 2024)
This article analyzes from the point of view of the philosophy of history the political movements carried out by reformers in the countries of the Middle East and the Turkestan region, as well as the processes of adaptation to the socio-historical conditions of such ideologies as pan-Islamism and pan-Turkism, which served as the reason for the activation of these movements.